Effektiewe toesighouding op eerstevlak as 'n voorvereiste vir doeltreffende personeelbenutting - Brand, Angus (School of Management Studies, 2024)
[No title page] The field of study is limited to the contribution of the first level supervisor in the public sector to the effective utilization of personnel under his supervision. Although the functions of the supervisor are much wider, specific aspects such as orientation, training and development, evaluation, communication, motivation, discipline and dealing with grievances are selected and separately subjected to careful examination.